2020
DOI: 10.3390/agronomy10030436
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of Eggplant Germplasm Evaluated under Open Field and Glasshouse Cropping Conditions

Abstract: Knowledge of agro-morphological genetic variation and cropping conditions on vegetative and yield-related traits plays a significant role in varietal improvement and production of eggplant (Solanum melongena L.). Following this premise, the current study was conducted to critically asses the genetic variation of 29 eggplant accessions by using agro-morphological characterization evaluated under two cropping conditions, namely, glasshouse and open field. The experiments were laid out in randomized complete bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Wide fruits have been reported for eggplant Epic grafted on to Beaufort [22], while cucumber Hady scion grafted onto Ferro rootstocks gave the highest value for this trait [23]. Fruit shape in eggplant has high heritability [1], and rootstocks influence fruit length and fruit diameter, possibly due to changes in the concentration of growth regulators induced by the rootstock.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wide fruits have been reported for eggplant Epic grafted on to Beaufort [22], while cucumber Hady scion grafted onto Ferro rootstocks gave the highest value for this trait [23]. Fruit shape in eggplant has high heritability [1], and rootstocks influence fruit length and fruit diameter, possibly due to changes in the concentration of growth regulators induced by the rootstock.…”
Section: Discussionmentioning
confidence: 99%
“…It differs in colour, shape and fruit size. The most widely cultivated type is the purple cultivars [1]. The colour depends on content of anthocyanins present in the fruit skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eggplant (Solanum melongena L.) is one of the important vegetable crop in South and South-East Asia 1 with 37% of the total cultivated area, and 53.31 million tons) production (worldwide (FAOSTAT, 2016). Major insect pests of eggplant are shoot and fruit borer (Leucinodesorbonalis Lepidoptera: Pyralidae), leafhopper (Amrascabiguttulabiguttula, Hemiptera, Cicadelloidea), white y (Bemiciatabaci,Hemiptera: Aleyrodidae), aphid (Aphis gossypii, Homoptera: Aphididae), thrips (Thripstabaci,Thysanoptera: Thripidae), etc 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The results are in concordance with those of Jirankali et al (2019) and Praneetha (2002) who observed variation among eggplant genotypes for marketable fruit yield. Eggplant germplasms have large genetic variation for agro-morphological characteristics including vegetative, yield, and yield components among the 29 accessions (Sulaiman et al, 2020). The adjusted fruit yield was found the highest in Parwanipur…”
Section: Fruit Weight Marketable Yield and Adjusted Yieldmentioning
confidence: 99%